Fueling Conflict? (De)Escalation and Bilateral Aid - Martin Gassebner; Richard Bluhm; Sarah Langlotz; Paul Schaudt (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
Civil conflicts undergo cycles of escalation. Beginning with riots, purges, and other violent acts of aggression, they escalate further and often culminate in outright civil war. This paper studies the effects of foreign aid on the escalation and de-escalation of conflict. We make three major contributions. First, we combine data on civil wars with data on low level conflicts in a new ordinal measure that captures the two-sided nature of conflict. Second, we study the effect of development aid on escalation and de-escalation. This allows us to give a rich description of how conflicts evolve dynamically, and to highlight the different roles played by bilateral aid in these transitions. We stress that low level conflicts matter since they are a violent expression of discontent over the distribution of rents (including aid) or of repression by the state. Third, we employ a new instrumental variable, which we then use to predict bilateral aid of DAC donor countries to 125 recipient countries over the period of 1975 to 2010. This solves the endogeneity concerns which have so far plagued the aid-conflict relationship. Our results show that the effect of foreign aid on the various transition probabilities is heterogeneous and sometimes very large. For example, receiving bilateral aid raises the chances of escalating from peace to small conflict, and from small conflict to armed conflict, but does not affect the transition from peace to civil war. Our main findings are robust to different estimation methods, controls and measures of conflict or foreign aid.
Keywords: O11; F35; D74; 330